2016
DOI: 10.1016/j.celrep.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Regulated IL-25 Increases Eosinophil Number to Provide Protection during Clostridium difficile Infection

Abstract: Summary Clostridium difficile infection (CDI) is the most common cause of hospital-acquired infection in the United States. Host susceptibility and the severity of infection are influenced by disruption of the microbiota and the immune response. However, how the microbiota regulates immune responses to mediate CDI outcome remains unclear. Here, we investigated the role of the microbiota-linked cytokine IL-25 during infection. Intestinal IL-25 was suppressed during CDI in humans and mice. Restoration of IL-25 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 46 publications
4
124
1
1
Order By: Relevance
“…In animal studies, Buonomo et al demonstrated a protective role of tissue eosinophils in mice, and this effect was mediated by IL-25 secretion. In this study, restoration of IL-25 levels in a murine model of C. difficile infection led to reduced mortality, whilst eosinophil depletion resulted in loss of the protection mediated by IL-25 [20]. In another study by the same group, C. difficile Binary toxin CDT ( C. difficile transferase) was able to induce inflammation in a murine model by binding to eosinophil Toll-like receptor 2 (TLR-2), resulting in activation of NFκB and suppression of eosinophil response via indirect induction of eosinophil apoptosis.…”
Section: Eosinophilsmentioning
confidence: 99%
“…In animal studies, Buonomo et al demonstrated a protective role of tissue eosinophils in mice, and this effect was mediated by IL-25 secretion. In this study, restoration of IL-25 levels in a murine model of C. difficile infection led to reduced mortality, whilst eosinophil depletion resulted in loss of the protection mediated by IL-25 [20]. In another study by the same group, C. difficile Binary toxin CDT ( C. difficile transferase) was able to induce inflammation in a murine model by binding to eosinophil Toll-like receptor 2 (TLR-2), resulting in activation of NFκB and suppression of eosinophil response via indirect induction of eosinophil apoptosis.…”
Section: Eosinophilsmentioning
confidence: 99%
“…Recently, Buonomo et al have reported that IL-25 also is protective against Clostridium difficile infection through eosinophil induction (24). Additionally, C. difficile infection with strains containing CDT ( Clostridium difficile transferase toxin) causes more severe pathology because they suppress the accumulation of eosinophils in the lamina propria of the colon (32).…”
Section: Discussionmentioning
confidence: 99%
“…Three readers blinded to the identity of the samples scored epithelial disruption (24). The scale was between 0 and 5.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry indicates that patients infected with C. difficile produce less IL-25 in colonic biopsies, a phenotype also observed in a mouse model of C. difficile -mediated colitis [12] . In this study, restoring IL-25 levels in mice increased survival via an unanticipated mechanism of eosinophil-dependent protection of the gut barrier (Figure 1).…”
Section: Tuft Cells In Diseasementioning
confidence: 99%
“…In this study, restoring IL-25 levels in mice increased survival via an unanticipated mechanism of eosinophil-dependent protection of the gut barrier (Figure 1). Moreover, treating mice with an anti-Siglec-F antibody ablated the protective phenotype of IL-25 [12] . Together, these data suggest that IL-25-mediated induction of eosinophils protects the host from C. difficile -induced disease.…”
Section: Tuft Cells In Diseasementioning
confidence: 99%